Proceedings of the International Conference of Early Childhood Education (ICECE 2017) 2018
DOI: 10.2991/icece-17.2018.11
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Students' Ability on Statistical Software Application (Public Service on Islamic Student for Early Childhood Education Program)

Abstract: Abstract--The aim of this project is to improve Islamic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
2
0
Order By: Relevance
“…Other similar findings from Al-Tannir et al (2018) also showed that training programs result in a marked increase in research knowledge and skills of the participants who were medical students. In the study of Reflianto (2017), the participants exhibited significant improvements after the training program on processing quantitative research data. Workshops that teach how to acquire knowledge from prior studies have been shown to improve basic research knowledge (Abdulghani et al, 2014;Mullan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other similar findings from Al-Tannir et al (2018) also showed that training programs result in a marked increase in research knowledge and skills of the participants who were medical students. In the study of Reflianto (2017), the participants exhibited significant improvements after the training program on processing quantitative research data. Workshops that teach how to acquire knowledge from prior studies have been shown to improve basic research knowledge (Abdulghani et al, 2014;Mullan et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…According to Arkkelin (2014), within the academic and business circles, SPSS is a common choice for understanding and interpreting research results. Reflianto (2017) wrote that the use of software tools such as SPSS in training activities increased data processing capability in quantitative research activities.…”
Section: Tools For Researchmentioning
confidence: 99%